Pelatihan Public Speaking Sebagai Upaya Peningkatan Kemampuan Berbicara di Depan Umum Anggota Pengurus Anak Cabang Fatayat Kecamatan Sadang Kabupaten Kebumen - Hamama, Syifa; Febriany, Febriany; Saputra, Restu Adi; Nurfadillah, Rizki (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2022)
Communication skills in the form of public speaking or commonly referred to as public speaking skills are skills that must be possessed by members of society. This is important because with good public speaking skills, they will be able to convey ideas, concepts, and information effectively. The problem is that many members of the Fatayat Sub-Branch Management of Sadang Village, Sadang District feel less or even unable to speak in public because they lack confidence, do not master the material, or do not understand how to do it. That is why Public Speaking training activities are held. This is expected to improve their skills. This activity is carried out in two stages, namely content delivery and practice. Based on the evaluation, the results obtained are very significant. With this activity, it is hoped that it can help develop and improve the ability and creativity in public speaking which can later be useful for members in social life in society and the work environment.